Prognostic Value of Metabolic Syndrome in Patients With Non-ST Elevated Myocardial Infarction Undergoing Percutaneous Coronary Intervention - Zhao, Li-Hong; Liu, Yin; Xiao, Jian-Yong; Wang, Ji-Xiang; Li, Xiao-Wei; Cui, Zhuang; Gao, Jing (Frontiers in Cardiovascular Medicine, 2022)
Objective We aim to investigate the prognostic effects of metabolic syndrome (MS) on patients with non-ST elevated myocardial infarction (NSTEMI) after percutaneous coronary intervention (PCI). Methods Patients with NSTEMI undergoing PCI were consecutively collected. According to the presence or absence of MS, they were divided into two groups and followed up for 1 year. The endpoint was major adverse cardiovascular events (MACE), including all-cause death, unstable angina hospitalization, heart failure (HF) hospitalization, non-fatal recurrent myocardial infarction (MI), and target lesion revascularization. Also, six subgroups were made according to gender, age, left ventricular ejection fraction (LVEF), Global Registry of Acute Coronary Events (GRACE) score, hypersensitive troponin (hsTNT), and several diseased vessels. Cox proportional hazard model was adopted to analyze the effect of MS on MACE in all the patients and different subgroups. Results A total of 1,295 patients were included in the current analysis and 660 (50.97%) of them had MS. About 88 patients were lost to follow-up, and the overall average follow-up was 315 days. MS was an independent risk factor for MACE (HR 1.714, CI 1.265–2.322, p = 0.001), all-cause death, heart failure (HF) hospitalization, and non-fatal recurrent MI. In the MS component, BMI ≥28 kg/m2 was positively associated with MACE. Subgroup analysis indicated the prognostic value of MS was more striking for patients with the following: age of >60, LVEF of ≤40%, GRACE of >140, multivessel disease, or hsTNT of >0.1 ng/ml. Conclusions The MS was a robust adverse prognostic factor in patients diagnosed with NSTEMI, especially among those of older age and at higher ischemic risk. A BMI of ≥28 kg/m2 independently predicted the occurrence of MACE. Prognosis may be improved by controlling abdominal obesity.